Factors Influencing Patient Decisions Regarding Treatments for Skin Growths: A Cross-Sectional Study - David G. Li; Fan Di Xia; Jasmine Rana; Grace J. Young; Forootan Alizadeh; Cara Joyce; Shinjita Das; Arash Mostaghimi (Dermatology Research and Practice)
Variations in treatment modalities for skin growths contribute substantially to overall healthcare spending within dermatology. However, little is known regarding factors impacting patient decision-making when choosing a treatment modality. In this survey-based, cross-sectional study (n = 375, 81.9% response rate), we asked patients to rate the importance of different treatment parameters for a nonfacial skin growth, further classified into five domains: efficacy, appearance, financial impact, visit duration, and productivity. Although patients generally prioritized treatment efficacy when selecting a treatment modality, they emphasized different aspects of the treatment experience as a function of age, gender, race, insurance status, and history of malignancy. Patients over age 50 were less likely to consider treatment impact on finances as being “important”, but more so efficacy and visit duration. Women were more likely to value efficacy and appearance. Patients without private insurance were more likely to cite efficacy and impact on productivity as being “important”. While the underlying reasons for these variations differ across patients, these findings help explain variations in treatment selection among patients choosing between treatments for skin growths and may ultimately lead to improved shared decision-making.